Fundamental Drivers of Capital Structure: Evidence from Publicly Traded Non-financial U.S. Firms - Sharif, Meskat Ibne (International Journal of Economics and Financial Issues, 2019)
This paper investigates the influence of relevant factors in determining capital structure with their respective extent. Excluding financial firms, all publicly traded American firms for the period of 1950-2005 are considered as the sample firms. Five fundamental factors that may explain leverage are growth opportunities, tangible assets, firm profit, firm size, and inflation. I use simple linear regression, BIC, and AIC, to identify the reliably consistent influential factors and a model. Using total leverage to market value of asset (TLMA) as my main model for the entire estimation period (1950-2005), I find that tangibility and firm size are significantly and positively related to leverage. The growth opportunities is also positively related to leverage but statistically insignificant. But firm profit has a significant negative relationship with leverage confirming the implication of the pecking order hypothesis. Keywords: static trade-off theory, pecking order theory, market timing theory, signaling theory, agency cost theory JEL Classifications: G1, G3, G10, G20, G32 DOI: https://doi.org/10.32479/ijefi.8663